2012
DOI: 10.1016/j.molcel.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coding of Insulin Action through Multiplexing of the AKT Pathway

Abstract: One of the unique characteristics of cellular signaling pathways is that a common signaling pathway can selectively regulate multiple cellular functions of a hormone; however, this selective downstream control through a common signaling pathway is poorly understood. Here we show that the insulin-dependent AKT pathway uses temporal patterns multiplexing for selective regulation of downstream molecules. Pulse and sustained insulin stimulations were simultaneously encoded into transient and sustained AKT phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(178 citation statements)
references
References 36 publications
16
155
1
Order By: Relevance
“…A precedent for differential effects of transient and prolonged insulin exposure comes from insulin's known mitogenic effects (20). Prolonged insulin exposure initiates signal transduction events that are distinct from transient incubation in cultured hepatocytes (29). However, the time scale in our in vivo experiments (2 vs. 8 h) is very CA expression in unfed larvae.…”
Section: Discussionmentioning
confidence: 91%
“…A precedent for differential effects of transient and prolonged insulin exposure comes from insulin's known mitogenic effects (20). Prolonged insulin exposure initiates signal transduction events that are distinct from transient incubation in cultured hepatocytes (29). However, the time scale in our in vivo experiments (2 vs. 8 h) is very CA expression in unfed larvae.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism may be related to the differential dose response relationship between pAkt and its various downstream substrates [48], or the temporal pattern of the insulin signal shown in modelling studies [51]. Insulin sensitivity by clamp was highly correlated with liver fat, adiponectin and Akt phosphorylation (R 0.53, 0.55 and 0.54, respectively [ESM Table 1]).…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction pathways utilise temporal signalling patterns, such as oscillations, to encode information of a greater complexity, with enhanced specificity for downstream substrates and processes (Cheong and Levchenko, 2010;Kubota et al, 2012). Self-organising oscillatory behaviour in PIP3 generation, facilitated by PI3K, has been described for amoeboid cells expressing the PH domain of Akt during random cell migration (Arai et al, 2010); however, such oscillations have not yet been demonstrated in response to insulin.…”
Section: Insulin Stimulation Induces Self-organising Oscillations In mentioning
confidence: 99%